2002
DOI: 10.1046/j.1365-2362.2002.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of apolipoprotein E polymorphism on plasma vitamin A and vitamin E levels

Abstract: Lipids do not mediate the effect of gender on vitamin A levels. Apolipoprotein E polymorphism is an independent determinant of vitamin A levels in women. Pending confirmation by others, we propose that enhancement of this vitamin may contribute to the beneficial impact of the epsilon2 allele on human ageing and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
(114 reference statements)
4
13
0
Order By: Relevance
“…Furthermore, the relationship between apo E variants and plasma concentration of a-tocopherol confirm previous findings (35,36). Indeed, as observed by Gomez-Coronado et al (35), we found that subjects bearing the E2 allele had lower a-tocopherol concentrations than those bearing the more common E3 allele. With the exception of the 4 E4-homozygous subjects, the subjects bearing the E4 allele had the higher a-tocopherol concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the relationship between apo E variants and plasma concentration of a-tocopherol confirm previous findings (35,36). Indeed, as observed by Gomez-Coronado et al (35), we found that subjects bearing the E2 allele had lower a-tocopherol concentrations than those bearing the more common E3 allele. With the exception of the 4 E4-homozygous subjects, the subjects bearing the E4 allele had the higher a-tocopherol concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…Our data suggest that the transport of a-tocopherol into the tissues may be altered by the apoE genotype, in which apoE4 show decreased a-tocopherol levels in tissues and increased levels in plasma. These data are supported by other reports showing increased plasma concentrations of a-tocopherol in apoE4 carriers [98,99].…”
Section: Antioxidant Supplysupporting
confidence: 91%
“…In our study, we found that patients with ε4+ at APOE had higher serum levels of ApoE and LDL-C, suggesting that SNPs at APOE are important contributors for the aggravation of CAD as they affect serum lipid levels. Meanwhile, APOE may also increase the risk of CAD through the interaction with the antioxidative and immune system [35], but more detailed mechanisms regarding the association of APOE and CAD need further investigation.…”
Section: Discussionmentioning
confidence: 99%